Analisis Yuridis Penjualan Objek Hak Tanggungan Tanpa Persetujuan Kreditur: Studi Putusan Mahkamah Agung Republik Indonesia Nomor 2973 K/Pdt/2024 tanggal 29 Agustus 2024 - Ghema Clara Natra; hasim purba; suprayitno (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The sale of mortgaged property by a debtor to a third party without the creditor’s consent is a recurring legal issue in Indonesian banking practice, creating conflicts between good-faith buyers and secured creditors. This study examines the validity of such transactions, legal protection for creditors and legal certainty based on Supreme Court Decision No. 2973 K/Pdt/2024. Using normative legal research, it finds that such sales may be voidable due to fraud, creditors are protected through registration principles and executorial rights and the decision reflects ongoing legal uncertainty due to the lack of comprehensive regulation governing conflicts between creditor rights and good-faith purchasers.